2020
DOI: 10.3389/fpsyg.2020.01352
|View full text |Cite
|
Sign up to set email alerts
|

Compromise Effect in Food Consumer Choices in China: An Analysis on Pork Products

Abstract: Compromise effect suggests that a product will have a higher chance to be chosen from a product choice set when its attributes are not the extremes (the best with the highest price or the worst with the lowest price). Few studies have examined compromise effect in food purchase. We investigate consumer pork purchase decision in the context of different decoy information intended to induce behavior and consider different presentation of decoy information. Furthermore, we explore compromise effect in relation to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 51 publications
2
8
0
Order By: Relevance
“…Schumpe et al (2020) found that setting text prompts as a decoy before shopping advertisements can divert the resistance of consumers to shopping advertisements, which is manifested as a greater willingness to purchase. Wu et al (2020) used traceable pork hindquarters as a study case and found that when consumers made consumption choices in a non-induced situation and then made choices in a situation with inductive information, the decoy effect was relatively stronger, while the direct creation of the decoy situation had a relatively small impact on the purchase selection behaviors of consumers.…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
“…Schumpe et al (2020) found that setting text prompts as a decoy before shopping advertisements can divert the resistance of consumers to shopping advertisements, which is manifested as a greater willingness to purchase. Wu et al (2020) used traceable pork hindquarters as a study case and found that when consumers made consumption choices in a non-induced situation and then made choices in a situation with inductive information, the decoy effect was relatively stronger, while the direct creation of the decoy situation had a relatively small impact on the purchase selection behaviors of consumers.…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
“…Notably, the social co-governance model based on stakeholder positive psychological capital is an approach suitable for analyzing food security and tourism poverty alleviation drawing on lessons from China (Wu et al, 2020 ). In this regard, the four ingredients of the social co-governance model are transplanted into the study of the food governance relationship chain involving national, industry, and enterprise practice seeking to alter consumer behavior and perception toward sustainable consumption for tourism poverty alleviation.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…National policy standards with a safety focus may also be part of corporate social responsibility (CSR) or industry safety and health standards practice to influence consumer choice. For the Chinese pork industry, the China Brand Name Association certifies products as voted trust brand (VTB) to assure consumers of their safety, reliability, quality, and affordability (Wu et al, 2020 ). Generally, this is dependent on internal and external factors that influence consumer decisions on food purchase behavior (Martínez-Ruiz and Gómez-Cant, 2016 ).…”
Section: Conceptual Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…The price elasticities, for example, may provide relevant support in these strategies and enable us to predict future patterns of food consumption [ 27 ]. The prices do indeed have a determinant impact on food markets [ 28 ], despite their particular price and income elasticities. In general, the food markets, specifically, those more linked with the production sector (agriculture), have lower, inelastic price elasticities.…”
Section: Literature Surveymentioning
confidence: 99%